Causes of unsuccessful ranibizumab treatment in exudative age-related macular degeneration in clinical settings - Cohen, Salomon Y; Oubraham, Hassiba; Uzzan, Joel; Dubois, Lise; Tadayoni, Ramin (Retina (Philadelphia, Pa.), 2012)
To identify the causes of loss of vision after ranibizumab therapy in patients with exudative age-related macular degeneration treated in three clinical settings. A retrospective multicentric analysis of 290 consecutive eyes comprising cohorts from 3 clinical settings showed that 21 eyes lost ≥ 15 letters on the Early Treatment Diabetic Retinopathy Study chart 1 year after the start of ranibizumab treatment. Fundus images of these eyes were analyzed by two independent readers to investigate the causes of visual loss. The three cohorts were compared. A search was made for factors predisposing to visual loss. A second analysis was performed to compare the baseline characteristics of patients who gained (visual acuity gainers) or lost (visual acuity losers) ≥ 15 letters. Among the 290 eyes included, the proportions from each center experiencing visual loss were not significantly different (mean, 7.24%, P = 0.2631). Mean visual loss of affected eyes was 27 letters. There was no significant difference between these eyes and others as regards age and gender of patients, laterality, type of choroidal neovascularization, number of visits, or initial visual acuity. Visual loss was secondary to the progression of atrophy in eight eyes, fibrosis in five eyes, a combination of fibrosis and atrophy in three eyes, severe subretinal hemorrhage in three eyes, and retinal pigment epithelial tear in two eyes. A significant difference between visual acuity gainers and losers was observed for 2 parameters: age of patients, 80.9 ± 5.3 years in visual acuity losers versus 77.5 ± 7.3 years in visual acuity gainers (P = 0.0473) and visual acuity at diagnosis, respectively, 56.2 ± 11.2 versus 49.0 ± 12.0 (P = 0.0288). Although uncommon, visual loss may occur during ranibizumab treatment and is because of the natural course of age-related macular degeneration in most cases.